Vaccination and Forms of Self-Protection in the Covid-19 Pandemic Maqashid Sharia Perspective: Perceptions of STAI Darul Arafah Students - Albani, Muhammad Syukri (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
In Indonesia, one of the ways to deal with the COVID-19 pandemic is the implementation of a vaccination program in which the implementation of this program has pros and cons in the community, one of the reasons is the level of effectiveness of the vaccine itself is still in doubt and the halalness of the product. Halal products are very important considering that the majority of the population in Indonesia is Muslim. This study focuses on the perceptions of STAI Darul Arafah students in interpreting the covid 19 vaccination as a form of self-preservation during a pandemic, the purpose of this study was to find out the extent of understanding and opinions of Stai Darul Arafah students in participating in the covid 19 vaccination program as a form of self-preservation. or self-preservation (Hifzu Nafsi). The final results of this study illustrate that the Indonesian government is considered quite good, even very good in the process of carrying out this Covid 19 vaccination. Regarding the vaccine used, the majority already believe in the efficacy of the Covid 19 vaccine, although there are still some respondents who do not fully believe that the Covid 19 vaccine is halal to use.